Development of archery test rig - Seow, Kok Foo (2013)
This thesis deals with the development of archery test rig. Test rig is a useful device as it is an apparatus used for assessing the performance of a piece of mechanical equipment. The main objective of this final year project is to design and fabricate an archery test rig for further study of the performance of a bow. This thesis describes the methods of designing and fabricating the mechanical part of the test rig. There are many steps taken to design and fabricate the mechanical parts of this test rig. The structural three-dimensional solid modeling of the test rig was developed by using the SolidWorks engineering drawing software. The fabrication process also undergoes many steps such as material marking, cutting, drilling, welding, grinding and finishing of the test rig by painting. The results of the testing of the performance of bow and how far the arrow can reach with certain applied tension on the bowstring also discussed in this thesis.